Synergistic roles of arbuscular mycorrhizal fungi and plant growth-promoting bacteria in sustainable agriculture and abiotic and biotic stress mitigation - Uniyal, Navendra (Ecological Questions, 2026)
Arbuscular mycorrhizal (AM) fungi form mutualistic associations with plant roots and play a critical role in regulating nutrient cycling, soil structure, and plant physiological performance in agricultural ecosystems. This review summarizes the functional roles of AM fungi in improving phosphorus uptake, enhancing soil aggregation, promoting bioremediation processes, and strengthening plant defense responses. In addition, the contributions of plant growth-promoting bacteria (PGPB) are discussed, particularly their ability to enhance nutrient solubilization, produce phytohormones, fix atmospheric nitrogen, and induce systemic tolerance against environmental stresses. Recent studies indicate that the combined application of AM fungi and PGPB results in improved nutrient availability, higher crop productivity, enhanced stress tolerance, and better soil biological activity compared to their individual use. Furthermore, this microbial consortium shows strong potential in mitigating abiotic stresses such as drought, salinity, and heavy metal contamination, as well as suppressing soil-borne pathogens. Overall, the integration of AM fungi and PGPB offers a biologically driven approach for improving soil fertility and crop performance, highlighting their importance in sustainable and climate-resilient agricultural systems.